Association Between Highly-Sensitive C- Reactive Protein and Neutrophil to Lymphocyte Ratio as Markers of Inflammation Among Adult Nigerians with Essential Hypertension - Udofia SS; Effiong JE; Iniobong EA; Emokpae MA (Annals of Health Research, 2023)
Background: Hypertension is a medical condition with global public health importance that is associated with significant morbidity and mortality in both developed and developing countries. It is important to identify readily available parameters that may indicate the level of inflammation that is associated with hypertension. Objective: To assess the relationship between highly-sensitive C-Reactive Protein (hs-CRP) and neutrophil-to-lymphocyte ratio (NLR) in hypertensive adults. Methods: Three hundred and sixty adults comprising 240 hypertensive and 120 healthy normotensive subjects (control) were studied. The full blood count (FBC) and highly-sensitive C-Reactive Protein (hs-CRP) levels were determined using standard methods. Results: The mean values of Total White Blood Cells count (WBC) (p = 0.03), absolute neutrophil count (p = 0.03), absolute lymphocyte count (p = 0.01), NLR (p = 0.001) and hs-CRP (p <0.001) in the hypertensive subjects were significantly higher than in the normotensive subjects. The mean values also differed significantly with increasing severity of hypertension. There was a significant but weak positive correlation between NLR and hs-CRP (r = 0.248, p <0.001). The Areas Under the Curve (AUC) of the Receiver Operating Characteristic (ROC) of NLR and hs-CRP (p = 0.01) were 0.68 and 0.639 respectively. Conclusion: NLR is closely associated with hs- CRP among hypertensive subjects. Therefore, NLR may be utilised routinely instead of hs-CRP as a screening test for inflammation in essential hypertension.